(untitled) (Indonesian Journal of Science and Technology, 2025)
This study explores the synthesis and application of water hyacinth-activated carbon (WHAC) as a counter-electrode in dye-sensitized solar cells (DSSCs). Characterization analyses, including X-ray diffraction, Raman spectroscopy, Fourier-transform infrared spectroscopy, and the N2 adsorption-desorption isotherm, confirmed the polycrystalline and mesoporous nature of WHAC, whose pore size and surface area are 3.06 nm and 176.7 m2/g, respectively. WHAC films deposited on the fluorine-doped tin oxide presented rough, random surface morphologies and thicknesses at higher concentrations. Optimized WHAC-based DSSCs presented a 1.40 ± 0.16% power conversion efficiency (PCE) compared to the 1.66 ± 0.26% presented by the standard platinum-based counter-electrodes. The efficiency improvement in the case of the WHAC-based DSSCs was the result of efficient electron transport, evident from the low sheet resistance and stable redox characteristics. The findings suggest WHAC is a promising and sustainable catalytic material for DSSC counter-electrodes.